Bodies of Information Intersectional Feminism and the Digital Humanities - Losh, Elizabeth; Wernimont, Jacqueline (Debates in the Digital Humanities, 2018)
A wide-ranging, interconnected anthology presents a diversity of feminist contributions to digital humanities In recent years, the digital humanities has been shaken by important debates about inclusivity and scope-but what change will these conversations ultimately bring about? Can the digital humanities complicate the basic assumptions of tech culture, or will this body of scholarship and practices simply reinforce preexisting biases? Bodies of Information addresses this crucial question by assembling a varied group of leading voices, showcasing feminist contributions to a panoply of topics, including ubiquitous computing, game studies, new materialisms, and cultural phenomena like hashtag activism, hacktivism, and campaigns against online misogyny. Taking intersectional feminism as the starting point for doing digital humanities, Bodies of Information is diverse in discipline, identity, location, and method. Helpfully organized around keywords of materiality, values, embodiment, affect, labor, and situatedness, this comprehensive volume is ideal for classrooms. And with its multiplicity of viewpoints and arguments, it's also an important addition to the evolving conversations around one of the fastest growing fields in the academy. Contributors: Babalola Titilola Aiyegbusi, U of Lethbridge; Moya Bailey, Northeastern U; Bridget Blodgett, U of Baltimore; Barbara Bordalejo, KU Leuven; Jason Boyd, Ryerson U; Christina Boyles, Trinity College; Susan Brown, U of Guelph; Lisa Brundage, CUNY; micha cárdenas, U of Washington Bothell; Marcia Chatelain, Georgetown U; Danielle Cole; Beth Coleman, U of Waterloo; T. L. Cowan, U of Toronto; Constance Crompton, U of Ottawa; Amy E. Earhart, Texas A&M; Nickoal Eichmann-Kalwara, U of Colorado Boulder; Julia Flanders, Northeastern U Library; Sandra Gabriele, Concordia U; Brian Getnick; Karen Gregory, U of Edinburgh; Alison Hedley, Ryerson U; Kathryn Holland, MacEwan U; James Howe, Rutgers U; Jeana Jorgensen, Indiana U; Alexandra Juhasz, Brooklyn College, CUNY; Dorothy Kim, Vassar College; Kimberly Knight, U of Texas, Dallas; Lorraine Janzen Kooistra, Ryerson U; Sharon M. Leon, Michigan State; Izetta Autumn Mobley, U of Maryland; Padmini Ray Murray, Srishti Institute of Art, Design, and Technology; Veronica Paredes, U of Illinois; Roopika Risam, Salem State; Bonnie Ruberg, U of California, Irvine; Laila Shereen Sakr (VJ Um Amel), U of California, Santa Barbara; Anastasia Salter, U of Central Florida; Michelle Schwartz, Ryerson U; Emily Sherwood, U of Rochester; Deb Verhoeven, U of Technology, Sydney; Scott B. Weingart, Carnegie Mellon U.